Enhanced Recovery Program after Cesarean Section in Sulaimani Maternity Teaching Hospital - Mohammed, Savinaz Abubakir; Khalis Jawad, Ariana; Jamal Murad, Srwa (Kurdistan Journal of Applied Research, 2020)
Enhanced recovery program (ERP) for cesarean section (C/S) is improving patient health and is cost-effective for healthcare providers. We aimed to assess how ERP improves patient satisfaction, ambulation time, severity of pain, decrease hospital stay among patients attending Sulaimani Maternity Teaching Hospital and fetal outcome. A quasi-experimental study was performed on 200 patients in Sulaimani from June 2019 to December 2019. The participants divided into two equal groups. The intervention group was 100 women who underwent elective C/S in Sulaimani Maternity Teaching Hospital and subjected to ERP. While the control group was the other 100 women who were not subjected to the ERP, and they were from the Emergency Department of the same hospital. The women in the intervention group were supervised by anesthetists from preoperatively, intraoperatively, through postoperatively. The intervention group showed significantly better outcome regarding time to ambulate; all patients were able to ambulate 4-5 hours postoperatively. Also, the duration of hospital stay was better in the intervention group; all the patients discharged before 24 hours, but five patients in the control group discharged after 24 hours. Besides, fetal Apgar score after five minutes was also better in the intervention group; at the first minute, the mean±SD (standard deviation) of Apgar score was 8.36±1.38 and 8.08±1.69 for the intervention, and control groups, respectively (P-value = 0.2). While at five minutes, the mean±SD of Apgar score was 9.59±064, and 8.96±1.12 for the intervention, and control groups, respectively (P-value = <0.001). This intervention had favorable outcomes regarding pain, time of ambulation, and fetal Apgar score. We recommend implementing ERP at a broader scale as it gives better outcomes.